Postoperative Radiotherapy for Patients With Resectable Stage III-N2 Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Lei, Tianyu; Li, Jing; Zhong, Hao; Zhang, Huibo; Jin, Yan; Wu, Jie; Li, Lan; Xu, Bin; Song, Qibin; Hu, Qinyong (Frontiers in Oncology, 2021)
Purpose For resectable cases of stage III-N2 non-small cell lung cancer (NSCLC), the best treatment after surgery is still uncertain. The effect of postoperative radiotherapy (PORT) is controversial. Thus, we performed this updated meta-analysis to reassess the data of PORT in stage III-N2 NSCLC patients, to figure out whether these patients can benefit from PORT. Methods We conducted searches of the published literature in EMBASE, PubMed, and the Cochrane Library for relevant randomized control trials (RCTs) comparing PORT group with the non-PORT group in NSCLC patients at stage III-N2. These studies allowed the prior chemotherapy in the treatment. We extracted the data from these articles and used the hazard ratios (HRs) and their 95% confidence intervals (CIs) as summary statistics for estimating the effect of PORT on overall survival (OS), disease-free survival (DFS), local-regional recurrence-free survival (LRFS). Result The analyses of seven randomized controlled trials (1,318 participants) show no benefit of PORT on survival (HR, 0.87; 95% CI, 0.71 to 1.07; p = 0.18) but a significantly different effect of PORT on DFS (HR, 0.83; 95% CI, 0.71 to 0.97; p = 0.02) and LRFS (HR, 0.64; 95% CI, 0.50 to 0.81; p = 0.0003). There is not enough evidence of a difference in the effect on survival by the utility of chemotherapy along with PORT though subgroup analysis of no chemotherapy group, concurrent chemoradiotherapy and sequential chemoradiotherapy group. Even in trials with 3D-CRT radiation technique, the pooled analysis shows no benefit of PORT on survival in patients with stage III-N2 NSCLC (data is not shown). Conclusion Our findings illustrate that in the postoperative treatment for patients with stage III-N2 NSCLC, PORT contributes to a significantly increased DFS and LR and may not associate with an improved OS, indicating a cautious selection.